2014
DOI: 10.3126/ijasbt.v2i4.11587
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Diets on Biology of Corcyra Cephalonica (Stainton) under Laboratory Condition in Chitwan, Nepal

Abstract: The experiments were conducted from 10th October, 2013 to 10th January, 2014 in Entomology Laboratory of National Maize Research Program, Rampur, Chitwan, Nepal at 26±2ºC and 70±5% RH in order to assess diet performance on the biological parameters of Corcyra cephalonica (Stainton). Four cereals namely corn, rice, millet and wheat were tested solely and mixed with groundnut. Among the eight treatments, corn + groundnut was superior diet in almost biological parameters of C. cephalonica followed by millet + gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…The maximum fecundity of 239.16 eggs/ female was recorded on maize (48.5%)+ sorghum (48.5%)+ groundnut (3%) diet and minimum fecundity 180.67 eggs/ female was found on wheat (100%). The current findings are in close agreement with those of Jhala et al (2019) and Bhandari and Regmi (2014) and Patel (2011). Lowest growth index (1.39) was recorded on wheat (100%) diet and significantly highest (2.66) on maize (48.5%) + sorghum (48.5%)+ groundnut (3%) diet (Table 1).…”
Section: Resultssupporting
confidence: 94%
“…The maximum fecundity of 239.16 eggs/ female was recorded on maize (48.5%)+ sorghum (48.5%)+ groundnut (3%) diet and minimum fecundity 180.67 eggs/ female was found on wheat (100%). The current findings are in close agreement with those of Jhala et al (2019) and Bhandari and Regmi (2014) and Patel (2011). Lowest growth index (1.39) was recorded on wheat (100%) diet and significantly highest (2.66) on maize (48.5%) + sorghum (48.5%)+ groundnut (3%) diet (Table 1).…”
Section: Resultssupporting
confidence: 94%
“…Although there were no reports to date indicating either of the insect species identified in stored sesame seeds in Ethiopia, our current findings were consistent with earlier research that suggested that C. cephalonica was noted as a significant sesame storage pest in India (Babu et al 2020;Dilipsundar et al 2019). Similar to this, C. cephalonica was also identified as a significant insect pest of many stored products in the tropics, affecting a variety of commodities, including oil seeds like groundnuts, cotton seeds, flax seeds, and oil-cakes (Bhandari et al 2014;Debbarma et al 2021;Vincent et al 2021). Typically, the destructive larval stage of C. cephalonica prefers to infest cracked or damaged grains, where it feeds beneath the formed silken threads, which over time gather density and bulk up the contaminated items (Chaudhuri and Senapati 2017).…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, the knowledge of the population trends, on the basis of the thermal conditions in the storage system, can be helpful for the management of alternative control methods, such as the use of natural enemies. Natural control methods can be offered by insect enemies belonging to the genera Trichogramma and Bracon (Bhandari et al, 2014). These valuable candidates may be involved in a biological control program, but one of the major difficulties is that their efficiency as pest management tools strongly depends on the time of release.…”
Section: Discussionmentioning
confidence: 99%
“…This is possible because the application of the model (1) provides for the estimation of the development rate functions parameters, which is made possible only using life tables data. Hence, once a valuable candidate is chosen among those proposed by Bhandari et al (2014) or Nasr et al (2015), a series of constant temperature rearing would enable their development rate function parameters to be estimated.…”
Section: Discussionmentioning
confidence: 99%